2017
DOI: 10.1002/anie.201609693
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Dearomatization of Naphthol Derivatives with Allylic Alcohols by Cooperative Iridium and Brønsted Acid Catalysis

Abstract: The combination of a transition-metal catalyst and organocatalyst was designed to achieve a highly enantioselective system for the allylic dearomatization reaction of naphthols with racemic secondary allylic alcohols. The desired β-naphthalenones, bearing an all-carbon quaternary center, were obtained in good yields with high chemo- and enantioselectivities. The cooperative catalytic system, involving a chiral iridium complex and phosphoric acid, provided measurable improvements in yields, and chemo- and enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(26 citation statements)
references
References 98 publications
(45 reference statements)
0
26
0
Order By: Relevance
“…Considering that naphthols are readily available starting materials that can be used to access functionalized chiral naphthalenones, we decided to investigate the feasibility of naphthol-derived vinyl ethers as potential substrates 9. Recently, You10 and Zhong11 reported the catalytic asymmetric allylic dearomatization (CADA) of naphthol derivatives 12. We anticipate that the same product would be generated if allyl naphthyl ethers undergo [1,3] O-to-C rearrangement under catalysis by the Cu( ii ) complex (Scheme 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that naphthols are readily available starting materials that can be used to access functionalized chiral naphthalenones, we decided to investigate the feasibility of naphthol-derived vinyl ethers as potential substrates 9. Recently, You10 and Zhong11 reported the catalytic asymmetric allylic dearomatization (CADA) of naphthol derivatives 12. We anticipate that the same product would be generated if allyl naphthyl ethers undergo [1,3] O-to-C rearrangement under catalysis by the Cu( ii ) complex (Scheme 1c).…”
Section: Resultsmentioning
confidence: 99%
“…[13] These methodologies can minimize the production of waste by-products and reaction steps, thereby making them atom-economic and environmental benign. [15] As a continuation of our efforts in chemoselective allylic substitution reactions, we report herein a palladium catalyzed mono-or di-selective allylation reaction of benzothiazolylacetate with allylic alcohols in good to excellent yields and selectivities. The substitution reaction could smoothly proceed by cooperative iridium and Brønsted acid catalysis, and afford the desired products in good results.…”
Section: Introductionmentioning
confidence: 96%
“…The substitution reaction could smoothly proceed by cooperative iridium and Brønsted acid catalysis, and afford the desired products in good results. [15] As a continuation of our efforts in chemoselective allylic substitution reactions, we report herein a palladium catalyzed mono-or di-selective allylation reaction of benzothiazolylacetate with allylic alcohols in good to excellent yields and selectivities.…”
Section: Introductionmentioning
confidence: 96%
“…Based on the pioneering works of Takeuchi 20,21 and Helmchen 22 , as well as the substantial contribution from Helmchen 23 , Hartwig 24 , Carreira 25 , You 26 and many other excellent scientists 2729 , iridium-catalyzed AA reactions show excellent branched selectivity, which distinguishes them from Pd-catalyzed processes 30 . Recent studies have indicated that iridium catalysis is compatible with many other catalysis modes (i.e., phase catalysis 31 , amine catalysis 3234 , Lewis base catalysis 35 , Brønsted acid catalysis 36 , and Lewis acid catalysis 3740 ), significantly expanding the scope of Ir-catalyzed asymmetric allylic alkylation (AAA) reactions 41 . Inspired by these impressive achievements, we question whether a synergetic catalysis strategy involving iridium catalysis can be adopted to resolve the remaining problem associated with Pd-catalyzed inverse electron-demand cycloadditions.…”
Section: Introductionmentioning
confidence: 99%